Faktor Yang Mempengaruhi Keluhan Musculoskeletal Disorder Pada Pekerja Penggilingan Padi Kabupaten Penajam Paser Utara - Wiranto, Agus; Ramdan, Iwan M; Lusiana, Dina (Politeknik Kesehatan Kemenkes Kalimantan Timur, 2019)
Rice milling is an informal sector which still lacks attention in terms of occupational health and safety aspects. Health problems experienced by one of them are complaints of musculoskeletal disorders (MSDs) which have an impact on decreasing work productivity. This study aims to determine the factors that influence complaints of musculoskeletal disorders (MSDs) in rice milling workers in Sepaku Sub-district, Penajam Paser Utara Regency. This research is a quantitative study with cross sectional research design. Sampling using purposive sampling method that amounted to 35 people. Data analysis used the rank-spearman test with a significance level of 0.05 (5%). The results showed that there was a significant relationship between work posture (p = 0,000) and the risk of manual handling material (MMH) (p = 0.005), with complaints of musculoskeletal disorders (MSDs). Whereas in the physical workload, there was no association with complaints of musculoskeletal disorders (MSDs) (p = 0.095). It is suggested for workers to do material manual handling (MMH) with the correct procedure, reduce awkward work postures during work and stretch the muscles before working and adequate rest so as to reduce fatigue and perceived muscle tension.